BRAZILIAN NURSING IN THE FIGHT AGAINST THE INFODEMIC DURING THE COVID-19 PANDEMIC - Samira Silva Santos Soares; Eloá Carneiro Carvalho; Thereza Christina Mó y Mó Loureiro Varella; Karla Biancha Silva de Adrade; Thaisa Dantas de Oliveira Souza; Norma Valéria Dantas de Oliveira Souza (Universidade Federal do Paraná, 2020)
Objective: to analyze, from publications on the Federal Nursing Council website, the lexicon related to the theme of "Fighting the infodemic during the Covid-19 pandemic". Method: a qualitative research of the documentary type, whose primary sources were reports and news published on the Federal Nursing Council website during the 2020 Nursing Week. Data was processed in the IRAMUTEQ® software. By means of the Descending Hierarchical Classification, the most frequent lexicon of the class that deals with the investigated theme was identified and it was processed from the word cloud. Result: the most frequent term identified was "desinformação" ("disinformation"). Conclusion: excess of information during the pandemic has caused disinformation, since many of the contents that circulate on social networks are inaccurate or false data, which hinders access to the legitimate information that the population and health professionals need at the current moment of the pandemic.